2020
DOI: 10.2147/dddt.s252681
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vivo Screening of Natural Products Against Angiogenesis and Mechanisms of Anti-Angiogenic Activity of Deoxysappanone B 7,4ʹ-Dimethyl Ether</p>

Abstract: Introduction The aim of this study was to screen the leading compounds of natural origin with anti-angiogenic potential and to investigate their anti-angiogenic mechanism preliminarily. Materials and Methods An initial screening of 240 compounds from the Natural Products Collection of MicroSource was performed using the transgenic zebrafish strain Tg [fli1a: enhanced green fluorescent protein (EGFP)] y1 . The zebrafish embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In vitro therapeutic index obtained by measuring compound`s cytotoxicity is commonly used to quantify the extent of the safety at the desired efficacious conditions of a single-or combination of compounds. The toxicity of mundulone has been previously reported on HEK293 cells and zebrafish embryo [64,65], however, mundulone acetate's toxicity is not reported. In the current study, mundulone by itself was found to be toxic at low concentrations (TI = 0.8).…”
Section: Discussionmentioning
confidence: 91%
“…In vitro therapeutic index obtained by measuring compound`s cytotoxicity is commonly used to quantify the extent of the safety at the desired efficacious conditions of a single-or combination of compounds. The toxicity of mundulone has been previously reported on HEK293 cells and zebrafish embryo [64,65], however, mundulone acetate's toxicity is not reported. In the current study, mundulone by itself was found to be toxic at low concentrations (TI = 0.8).…”
Section: Discussionmentioning
confidence: 91%
“…In multiple studies on angiogenesis, it has been reported that there is a SLIT3-ROBO4 pathway. 50 , 59 61 Studies in vascular endothelial cells have shown that ligand SLIT3 inhibits ROBO4 shedding to enhance ROBO4 signaling. 62 In the present study, we found that the increased expression of SLIT3 and ROBO4 induced by TG were significantly inhibited by SLIT3-specific siRNA, indicating that TG induced ER stress enhanced ROBO4 expression by SLIT3.…”
Section: Discussionmentioning
confidence: 99%
“…However, the two flavones had never been isolated before, and their biological functions remain to be clarified. Interestingly, analogs of the two flavones, deoxysappanone B 7,4′-dimethyl ether, deoxysappanone B 7,3′-dimethyl ether acetate, and 5,7-dihydroxy-3′,4′-dimethoxyflavone have been demonstrated to have anti-cryptosporidial [ 25 ], anti-angiogenic [ 26 ] or antibacterial [ 27 ] activity. Therefore, isolation and purification of the two new flavones from AEE to determine whether they have similar antibacterial or antiviral activities are needed in the future.…”
Section: Discussionmentioning
confidence: 99%